Spatial estimation of flood residual water cultivation (FRWC) potential for food security in Sédhiou and Tambacounda regions of Sénégal - Nguru, Wilson; Abera, Wuletawu; Ouedraogo, Issa; Chege, Christine Gacheri Kiria; Kane, Babacar; Bougouma, Katiana; Mwongera, Caroline (Elsevier, 2023)
Nearly 90% of farming households in Senegal rely on rainfed agriculture; in recent years, climate change-induced disruptions to rainfall patterns and the ensuing depletion of water resources have had adverse effects on agricultural production, livelihoods, and food security. Recent studies recommend further assessment of the viability of and potential for Flood Residual Water Cultivation (FRWC) as an alternative growing strategy (i.e., to supplement or extend natural growing seasons). This study utilizes satellite imagery, GIS mapping, and crop analysis to identify areas with high potential for FRWC in Senegal's Sédhiou and Tambacounda regions, and recommends key crops that can be grown using FRWC and support food security. By calculating the Normalized Difference Water Index (NDWI) values based on historical data for the rainy season (September) and the first dry month after the rainy season (November) over a 9-year period, areas with flooding potential were identified and mapped. To assess the crop-growing potential for these mapped areas, we used crop reference evapotranspiration (ET) and determined daily water requirements for the select crops included in our analyses. indicated suitable FRWC areas along river valleys in both regions, with specific locations identified along the Gambia River, the Senegal River in the Bakel Department, and low-lying plains near Kidira and Gourel Bouri. It was observed that regions closer to the Sahara Desert required more water for crop production due to higher temperatures and evapotranspiration rates. Our study identified a total potential FRWC area of 20.7 km² and recommends short-duration crops like okra, French beans, and drought-tolerant crops such as sorghum for FRWC. The integration of FRWC with climate-smart management practices can aid in climate adaptation and economic empowerment in the studied regions, and in Sub-Saharan Africa at large.